Rancang Bangun Prototype Home Security System Menggunakan RFID Berbasis SMS Gateway dan Notifikasi Telepon - Aidilvi Prya Pratama Azwar; Arnes Sembiring; Kalvin Chiuloto (Forum Kerjasama Pendidikan Tinggi, 2023)
This study develops RFID technology for a home security system, which is to make a home security system that is minimal in error and is also more stringent than just security that is carried out in general. By utilizing RFID technology coupled with a magnetic switch sensor based on SMS gateway and telephone notification, it is hoped that this research will produce a prototype tool in the form of a home security system. This prototype will be made using an Arduino Nano-based microcontroller which will be connected to several sensors and modules. The test results show that this system can provide accurate information to homeowners and can open doors with an RFID key.